Real-world experience comparing two common left atrial appendage closure devices - Fastner, Christian; Behnes, Michael; Lang, Siegfried; Borggrefe, Martin; Akın, Ibrahim (BMC cardiovascular disorders, 2018)
The interventional left atrial appendage closure (LAAC) is a guideline-conform alternative to oral anticoagulation (OAC) in non-valvular atrial fibrillation patients with OAC ineligibility. It was aimed to directly compare two contemporary devices in a real-world patient population.
Gesehen am 24.08.2018